Taking your iPad to the max : a concise introduction for the intelligent iPad user - Sadun, Erica; Grothaus, Michael; Sande, Steve (New York : Apress L. P., 2010)
Annotation Fast, fun, and full of facts,Take Your iPad to the Maxgives you the tips and techniques you need to get the most out of your new iPad. Apple's latest device is much more than a big iPhone, and this book will help you master the new category of touch-driven productivity apps developed specifically for the iPad, including the iWork App Suite. You'll also learn all about the built-in apps, including Mail, Calendar, and iTunes, as well as the brand-new iBooks. And, of course, you'll get all of the advanced shortcuts and techniques that will leave fellow iPad users in the dust.Author and gadget hackerErica Sadun'senthusiasm for Apple devices and tools is infectiously catching. At the same time, her expertise and ability to uncover undocumented features and share them with her readers has made her something of a legend. Fortunately, Erica likes to share everything she knows with you, her loyal reader, and she knows just how to explain everything in clear, enjoyable-to-read prose.What you'll learnHow to handle multitouch interface fundamentalsHow to use all the built-in apps, including Mail, Calendar, Safari, and the new iWork SuiteHow to use iTunes and iBooks to open a world of expansion and personalizationHow to use your iPad over WiFi and take advantage of free services like VoIP telephonyHow to integrate your iPad with your network and other mobile and tethered devicesWho this book is forFor every iPad owner who wants the fastest introduction, crammed with most useful information, presented in an extremely enjoyable style.Table of ContentsBringing home the iPad: Purchase decisions, model choicesConnecting to iTunes: How to set up your system using iTune' configuration tools.Exploring the iPad hardware: Powering the device on and off, exploring its sensorsInteracting with your iPad: Learning the touch-based vocabulary of the iPad, Manipulating the home screen, Spotlight, AccessibilityConnecting to the Internet: An introduction to using WiFi and/or 3GsBrowsing with Mobile Safari. A complete how-to for using Safari.Touching your Music and Video. Including iPod features, Video, & YouTubeShopping at the App Store, Music Store, and Book StoreUsing iBooksLeveraging your Desk Set: Notes, Contacts and Calculator, Clock, CalendarSetting up and using EmailWorking with MapsTaking your Photos With YouOn the go with iWork: Creating and viewing documents, spreadsheets, etc.5 other great ways to use your iPad